First aid for the internal medicine boards - Le, Tao (McGraw-Hill Medical, 2011)
"A high-yield insider's guide to passing the internal medicine board examination -- written by physicians who passed. New FULL-COLOR design! 5 STAR DOODY'S REVIEW "I wish I had this book when I was studying for my boards. It is well worth the price for both study for the boards and for a quick reference." -- Doody's Review Service (reviewing a previous edition) Perfect for last minute review as well as recertification, First Aid for the Internal Medicine Boards delivers the high-yield information, mnemonics, and visual aids need for exam success. The third edition is distinguished by a new full-color presentation, new integrated mini-cases that put clinical information in context, more algorithms and tables comparing and contrasting diseases and disorders with similar presentations, and valuable clinical pearls. All content is based on the most recently adminstered in-service and board exams so you know you are studying the most relevant, up-to-date material possible. The content you need to ace the exam."--Provided by publisher.